Mental wellbeing effects of disclosing life events on social media - Koustuv Saha; Dong Whi Yoo; Vedant Das Swain; Munmun De Choudhury (Scientific Reports)
Abstract Life events are noteworthy moments that we often share on social media. However, how such online disclosures of life events impact our mental wellbeing is largely unknown. This study examines the effects of these disclosures using data from 236 participants. Regression models reveal that individual differences and event attributes significantly influence wellbeing. Through a quasi-experimental design, we find that sharing life events on Facebook positively impacts wellbeing by increasing positive affect and sleep quality while reducing negative affect, stress, and anxiety. Notably, disclosing negative events shows the strongest improvement in wellbeing, suggesting a protective effect of social media. Additionally, life event disclosures elicit more reactions and comments than other Facebook posts, with negative events receiving more comments but fewer reactions than non-negative life event disclosures. These findings offer insights into the complex relationship between online disclosures and wellbeing, contributing to theoretical understanding and practical strategies for enhancing online experiences and supporting mental health.